(3bghI GdEfTGAs - (3CHh HcQ Hf Ydj Hf YHO Gddg GdMehj GdCRQGQj, Jbj GdOjf GHf MLI,J (B837 (3g` s
(3ChdgG (B:s
(3LYdge Ydi WQjb GdeQGabI HJMbjb GdehGabI haj JUMjM GdeSGFd JQLjM GdOdGFd s
(3BNQgG (B:s
(3aEf Chdi ef Qad aj Mdd GfYGefG GdTQja ef hLH Mbg YdjfG hCYOfG s
(3ocJHJ GdYfhGfGJ HGdMeQIs
(3hHgG fXGe GdJYbjHIs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B67s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B130 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1366s
Keywords: (3GdCOHs